Construction of 1D/0D/2D Zn0.5Cd0.5S/PdAg/g-C3N4 ternary heterojunction composites for efficient photocatalytic hydrogen evolution. (15th January 2022) - Lou, Yaqin; Fei, Ting; Zhang, Yiwei; Dong, Guomeng; Deng, Qinghua; Zhou, Yuming; Mao, Chunfeng
Abstract: A high-efficiency and easy-available approach was developed to obtain a ternary heterojunction composites with advanced hydrogen evolution reaction (HER) performance under visible light by water split. PdAg bimetallic nanoparticles make a close contact interface between g-C3 N4 (CN) and Zn0.5 Cd0.5 S(ZCS). Under visible light irradiation, CN and ZCS are both excited to generate electron-hole pairs, PdAg bimetallic nanoparticles act as a bridge between CN and ZCS. Not only can the photogenerated electrons from CN be captured, but they can also be quickly transferred to the surface of ZCS and participate in the photocatalytic reaction to release H2, and the recombination of charge carriers between the contact interface of ZCS and CN can be significantly inhibited. In addition, the thin CN layer reduces the photocorrosion of the ZCS and enhances the specific surface area of the composite material. After testing, the composite material with 30 wt% ZCS and 4 wt% PdAg demonstrates hydrogen evolution performance, up to 6250.7 μmol g −1 h −1, which is 753 times the hydrogen evolution rate of single-component CN and 12.6 times of ZCS/CN. Compared with single-component and two-component photocatalysts, the ternary ZCS/PdAg/CN photocatalyst achieves significantly enhanced photocatalytic activity. Highlights: The composite material with 30 wt% Zn0.5 Cd0.5 S and 4 wt% PdAg presents excellent H2 production (6250.7 μmol/g·h). 1D/0D/2D ZCS/PdAg/CN ternary heterojunction composites inhibits the recombination of photogenerated carriers. PdAg can act as an electron transport medium to accelerate utilization of light-induced electrons. The possible catalytic mechanism of photocatalytic hydrogen production by ZCS/PdAg/CN is proposed.